Precalculus

#$&*

course Mth 272

6/7 around 10:45

Question: `q001 A straight line connects the points (3, 5) and (7, 17), while another straight line continues on from (7, 17) to the point (10, 29). Which line is steeper and on what basis to you claim

your result?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

When you find the slope of the first set of points by using the equation (y2 - y1) / (x2 - x1) it would

be (17-5)/(7-3) which is 12/4 = 3. The slope for the second set of points is calculated as (29-17)/(10

-7) which is 12/3 = 4 Therefore, the second set of points has a steeper slope because it has a steeper

rise. A slope of 4 is steeper than a slope of 3.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aThe point (3,5) has x coordinate 3 and y coordinate 5. The point (7, 17) has x coordinate 7 and y

coordinate 17. To move from (3,5) to (7, 17) we must therefore move 4 units in the x direction and 12

units in the y direction.

Thus between (3,5) and (7,17) the rise is 12 and the run is 4, so the rise/run ratio is 12/4 = 3.

Between (7,10) and (10,29) the rise is also 12 but the run is only 3--same rise for less run, therefore

more slope. The rise/run ratio here is 12/3 = 4.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `q002. The expression (x-2) * (2x+5) is zero when x = 2 and when x = -2.5. Without using a

calculator verify this, and explain why these two values of x, and only these two values of x, can make

the expression zero.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

1. Set the equation to 0: 0=(x-2)(2x+5)

2. Foil the equation: 0= 2x^2 + x -10

3. Factor out 2: 0 = 2 (x^2 + 1/2x - 5)

4. Find the two values that can be multipled to get the answer of -5, and added to get the answer of

1/2.

5. -2.5 + 2 = 1/2 and 2 * -2.5 = -5

6. We can conclude that for this equation, when y=0 x =2 and -2.5. This equation is to a second degree,

so it is a parabola. It makes sense that there are two zeros on this function.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aIf x = 2 then x-2 = 2 - 2 = 0, which makes the product (x -2) * (2x + 5) zero.

If x = -2.5 then 2x + 5 = 2 (-2.5) + 5 = -5 + 5 = 0.which makes the product (x -2) * (2x + 5) zero.

The only way to product (x-2)(2x+5) can be zero is if either (x -2) or (2x + 5) is zero.

Note that (x-2)(2x+5) can be expanded using the Distributive Law to get

x(2x+5) - 2(2x+5). Then again using the distributive law we get

2x^2 + 5x - 4x - 10 which simplifies to

2x^2 + x - 10.

However this doesn't help us find the x values which make the expression zero. We are better off to

look at the factored form.

STUDENT QUESTION

I think I have the basic understanding of how x=2 and x=-2.5 makes this equation 0

I was looking at the distributive law and I understand the basic distributive property as stated in

algebra

a (b + c) = ab + ac and a (b-c) = ab - ac

but I don’t understand the way it is used here

(x-2)(2x+5)

x(2x+5) - 2(2x+5)

2x^2 + 5x - 4x - 10

2x^2 + x - 10.

Would you mind explaining the steps to me?

INSTRUCTOR RESPONSE

The distributive law of multiplication over addition states that

a (b + c) = ab + ac

and also that

(a + b) * c = a c + b c.

So the distributive law has two forms.

In terms of the second form it should be clear that, for example

(x - 2) * c = x * c - 2 * c.

Now if c = 2 x + 5 this reads

(x-2)(2x+5) = x * ( 2 x + 5) - 2 * (2 x + 5).

The rest should be obvious.

We could also have used the first form.

a ( b + c) = ab + ac so, letting a stand for (x - 2), we have

(x-2)(2x+5) = ( x - 2 ) * 2x + (x - 2) * 5.

This will ultimately give the same result as the previous. Either way we end up with 2 x^2 + x - 10.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):The given solution find the zeros in the equation's binomial form, while

my method does the opposite. It takes the equation from the ax^2 + bx + c form to find the values for

its binomial form.

------------------------------------------------

Self-critique Rating: 3

*********************************************

Question: `q003. For what x values will the expression (3x - 6) * (x + 4) * (x^2 - 4) be zero?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

1. Set all three equations to 0

0=3x-6, 6=3x, x=2

0=x+4, x=-4

0=x^2 - 4, 4 = x^2, sqrt(4)=sqrt(x^2), x= 2 and -2

If you multiply this equation you can see that it is a 4th degree function.

3x^4 + 6x^3 -36x^2 -24x +96

This tells us that there will be four zeros

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aIn order for the expression to be zero we must have 3x-6 = 0 or x+4=0 or x^2-4=0.

3x-6 = 0 is rearranged to 3x = 6 then to x = 6 / 3 = 2. So when x=2, 3x-6 = 0 and the entire product

(3x - 6) * (x + 4) * (x^2 - 4) must be zero.

x+4 = 0 gives us x = -4. So when x=-4, x+4 = 0 and the entire product (3x - 6) * (x + 4) * (x^2 - 4)

must be zero.

x^2-4 = 0 is rearranged to x^2 = 4 which has solutions x = + - `sqrt(4) or + - 2. So when x=2 or when x

= -2, x^2 - 4 = 0 and the entire product (3x - 6) * (x + 4) * (x^2 - 4) must be zero.

We therefore see that (3x - 6) * (x + 4) * (x^2 - 4) = 0 when x = 2, or -4, or -2. These are the only

values of x which can yield zero.**

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `q004. One straight line segment connects the points (3,5) and (7,9) while another connects

the points (10,2) and (50,4). From each of the four points a line segment is drawn directly down to the

x axis, forming two trapezoids. Which trapezoid has the greater area? Try to justify your answer with

something more precise than, for example, 'from a sketch I can see that this one is much bigger so it

must have the greater area'.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

The second trapezoid would have the greater area because the distance between the points is greater

than that of the first trapezoid. If I remember correctly, the distance formula is (x1 + x2) / 2 and

(y1 + y2) / 2. If we use that equation on the first set of points, we see that the distance between the

x-points is 5 and the distance between the y-points is 7.5. For the second set of points, the distance

between the x-points is 30 and the distance between the y-points is 3. We can conclude that the second

set of points has a trapezoid with a greater area.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aYour sketch should show that while the first trapezoid averages a little more than double the

altitude of the second, the second is clearly much more than twice as wide and hence has the greater

area.

To justify this a little more precisely, the first trapezoid, which runs from x = 3 to x = 7, is 4

units wide while the second runs from x = 10 and to x = 50 and hence has a width of 40 units. The

altitudes of the first trapezoid are 5 and 9,so the average altitude of the first is 7. The average

altitude of the second is the average of the altitudes 2 and 4, or 3. So the first trapezoid is over

twice as high, on the average, as the first. However the second is 10 times as wide, so the second

trapezoid must have the greater area.

This is all the reasoning we need to answer the question. We could of course multiply average altitude

by width for each trapezoid, obtaining area 7 * 4 = 28 for the first and 3 * 40 = 120 for the second.

However if all we need to know is which trapezoid has a greater area, we need not bother with this

step.

*********************************************

Question: `q005. Sketch graphs of y = x^2, y = 1/x and y = `sqrt(x) [note: `sqrt(x) means 'the square

root of x'] for x > 0. We say that a graph increases if it gets higher as we move toward the right, and

if a graph is increasing it has a positive slope. Explain which of the following descriptions is

correct for each graph:

As we move from left to right the graph increases as its slope increases.

As we move from left to right the graph decreases as its slope increases.

As we move from left to right the graph increases as its slope decreases.

As we move from left to right the graph decreases as its slope decreases.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

For the graph of y=x^2, the graph is increasing and its slope is increasing as well. For example, when

we must from x=1 to x=2, the slope is 3, but when we move from x=2 to x=3, the slope is 5.

For the graph of y=1/x, the graph is decreasing and the slope is decreasing for each x-value because

the y-values decrease by less and less each time.

For the graph of y=sqrt(X), the graph is increasing as the slope decreases because as the x-values

increase, the difference between the y-values becomes less and less.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aFor x = 1, 2, 3, 4:

The function y = x^2 takes values 1, 4, 9 and 16, increasing more and more for each unit increase in x.

This graph therefore increases, as you say, but at an increasing rate.

The function y = 1/x takes values 1, 1/2, 1/3 and 1/4, with decimal equivalents 1, .5, .33..., and .25.

These values are decreasing, but less and less each time. The decreasing values ensure that the slopes

are negative. However, the more gradual the decrease the closer the slope is to zero. The slopes are

therefore negative numbers which approach zero.

Negative numbers which approach zero are increasing. So the slopes are increasing, and we say that the

graph decreases as the slope increases.

We could also say that the graph decreases but by less and less each time. So the graph is decreasing

at a decreasing rate.

For y = `sqrt(x) we get approximate values 1, 1.414, 1.732 and 2. This graph increases but at a

decreasing rate.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: OK

*********************************************

Question: `q006. If the population of the frogs in your frog pond increased by 10% each month, starting

with an initial population of 20 frogs, then how many frogs would you have at the end of each of the

first three months (you can count fractional frogs, even if it doesn't appear to you to make sense)?

Can you think of a strategy that would allow you to calculate the number of frogs after 300 months

(according to this model, which probably wouldn't be valid for that long) without having to do at least

300 calculations?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

This would be the type of problem where you would need to use this type of equation to find the answer:

y=a * b ^ (x), where a is the starting number, b is the rate each month's frog population increases by,

and x is the number of months you are trying to find the answer for. To find out how many frogs there

would be after 300 months, we would do y = 20 * 1.10 ^ (300) which gives you 5.23 * 10^13 frogs.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aAt the end of the first month, the number of frogs in the pond would be (20 * .1) + 20 = 22 frogs. At

the end of the second month there would be (22 * .1) + 22 = 24.2 frogs while at the end of the third

month there would be (24.2 * .1) + 24.2 = 26.62 frogs.

The key to extending the strategy is to notice that multiplying a number by .1 and adding it to the

number is really the same as simply multiplying the number by 1.1. We therefore get

20 * 1.1 = 22 frogs after the first month

22 * 1.1 = 24.2 after the second month

etc., multiplying by for 1.1 each month.

So after 300 months we will have multiplied by 1.1 a total of 300 times. This would give us 20 *

1.1^300, whatever that equals (a calculator, which is appropriate in this situation, will easily do the

arithmetic).

A common error is to say that 300 months at 10% per month gives 3,000 percent, so there would be 30 *

20 = 600 frogs after 30 months. That doesn't work because the 10% increase is applied to a greater

number of frogs each time. 3000% would just be applied to the initial number, so it doesn't give a big

enough answer.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: OK

*********************************************

Question: `q007. Calculate 1/x for x = 1, .1, .01 and .001. Describe the pattern you obtain. Why do we

say that the values of x are approaching zero? What numbers might we use for x to continue approaching

zero? What happens to the values of 1/x as we continue to approach zero? What do you think the graph of

y = 1/x vs. x looks for x values between 0 and 1?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

1/1 = 1, 1/.1=10, 1/.01=100, and 1/.001=1000. The pattern is that as the decimal gets smaller, when you

divide by 1 the result will be multipled by 10. The values of x are approaching 0 because they are

continually getting smaller..1 is 1/10 of 1, .01 is 1/100 of 1, and so on. The numbers we would use to

continue to approach 0 would be .0001 and .00001. The first one is 1/10,000 of 1 and the second one is

1/100,000 of one. For the values between 0 and 1, the graph would be decreasing at a decreasing rate

and the slope would be getting less steep.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aIf x = .1, for example, 1 / x = 1 / .1 = 10 (note that .1 goes into 1 ten times, since we can count

to 1 by .1, getting.1, .2, .3, .4, ... .9, 10. This makes it clear that it takes ten .1's to make 1.

So if x = .01, 1/x = 100 Ithink again of counting to 1, this time by .01). If x = .001 then 1/x = 1000,

etc..

Note also that we cannot find a number which is equal to 1 / 0. Deceive why this is true, try counting

to 1 by 0's. You can count as long as you want and you'll ever get anywhere.

The values of 1/x don't just increase, they increase without bound. If we think of x approaching 0

through the values .1, .01, .001, .0001, ..., there is no limit to how big the reciprocals 10, 100,

1000, 10000 etc. can become.

The graph becomes steeper and steeper as it approaches the y axis, continuing to do so without bound

but never touching the y axis.

This is what it means to say that the y axis is a vertical asymptote for the graph .

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): The difference between the given answer and my answer is that it mentions

that the y-axis is a vertical asmyptote because dividing x by 0 is undefined, so the graph will never

touch the y-axis.

------------------------------------------------

Self-critique Rating: 3

*********************************************

Question: `q008. At clock time t the velocity of a certain automobile is v = 3 t + 9. At velocity v its

energy of motion is E = 800 v^2. What is the energy of the automobile at clock time t = 5?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I evaluated v at t=5. 3(5)+9=24. Then I evaluated the calculated v-value at v=24, because that is

the calculated velocity for t=5. 800 * 24^2 = 460,800.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aFor t=5, v = 3 t + 9 = (3*5) + 9 = 24. Therefore E = 800 * 24^2 = 460800.

*********************************************

Question: `q009. Continuing the preceding problem, can you give an expression for E in terms of t?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

E = 800 * (3t+9)^2

confidence rating #$&*:2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aSince v = 3 t + 9 the expression would be E = 800 v^2 = 800 ( 3t + 9) ^2. This is the only answer

really required here.

For further reference, though, note that this expression could also be expanded by applying the

Distributive Law:.

Since (3t + 9 ) ^ 2 = (3 t + 9 ) * ( 3 t + 9 ) = 3t ( 3t + 9 ) + 9 * (3 t + 9) = 9 t^2 + 27 t + 27 t +

81 = 9 t^2 + 54 t + 81, we get

E = 800 ( 9 t^2 + 54 t + 81) = 7200 t^2 + 43320 t + 64800 (check my multiplication because I did that

in my head, which isn't always reliable).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

I wasn't sure what the question meant by ""E in terms of t"" but I considered what I did in the previous

problem to get to my answer. Now that I look at the given solution, I notice that the equation could

have been further expandeded using the distributive law.

------------------------------------------------

Self-critique Rating:3

*********************************************

Question: For what x values is the value of the expression (2^x - 1) ( x^2 - 25 ) ( 2x + 6) zero?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Set everything equal to 0

0=2^x-1, 1=2^x, log(1) = log(2x), x = log(1)/log(2)

0=x^2-25, sqrt(25)=sqrt(x^2), x = 5 and -5

0=2x+6, -6=2x, x = -3

The zeros are log(1)/log(2), 5, -5, and -3.

@&

log(1) has a very specific and known value which allows you to determine log(1) / log(2), even though if (as would be expected) you don't happen to know log(2).

*@

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

*********************************************

Question: One straight line segment connects the points (3,5) and (7,9) while another connects the

points (3, 10) and (7, 6). From each of the four

points a line segment is drawn directly down to the x axis, forming two trapezoids. Which trapezoid has

the greater area?

Any solution is good, but a solution that follows from a good argument that doesn't actually calculate

the areas of the two trapezoids is better.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Using the distance formula, we see that the distance between the first set of points is (5, 7.5) and

the distance between the second set of points is (5, 8). Since the second set of points have a greater

distance between each other, I would say that this will be the trapazoid with the greater area because

it has larger dimensions.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

*********************************************

Question:

Suppose you invest $1000 and, at the end of any given year, 10% is added to the amount. How much would

you have after 1, 2

and 3 years?

What is an expression for the amount you would have after 40 years (give an expression that could

easily be evaluated using a calculator, but don't bother to actually evaluate it)?

What is an expression for the amount you would have after t years?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

The equation for this in the form of y=a * b^x is t = 1000 * 1.10^x.

1 year = 1,100

2 years = 1,210

3 years = 1,331

40 years = 40,259.26

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

------------------------------------------------

Self-critique Rating: 3"

&#Good responses. See my notes and let me know if you have questions. &#